Quantifying warfighter performance in a target acquisition and aiming task using wireless inertial sensors. (September 2016) - Davidson, Steven P.; Cain, Stephen M.; McGinnis, Ryan S.; Vitali, Rachel R.; Perkins, Noel C.; McLean, Scott G.
Abstract: An array of inertial measurement units (IMUS) was experimentally employed to analyze warfighter performance on a target acquisition task pre/post fatigue. Eleven participants (5M/6F) repeated an exercise circuit carrying 20 kg of equipment until fatigued. IMUs secured to the sacrum, sternum, and a rifle quantified peak angular velocity magnitude (PAVM) and turn time (TT) on a target acquisition task (three aiming events with two 180° turns) within the exercise circuit. Turning performance of two turns was evaluated pre/post fatigue. Turning performance decreased with fatigue. PAVMs decreased during both turns for the sternum ( p  < 0.001), sacrum ( p  = 0.007) and rifle ( p  = 0.002). TT increased for the sternum ( p  = 0.001), sacrum ( p  = 0.003), and rifle ( p  = 0.02) during turn 1, and for the rifle ( p  = 0.04) during turn 2. IMUs detected and quantified changes in warfighter aiming performance after fatigue. Similar methodologies can be applied to many movement tasks, including quantifying movement performance for load, fatigue, and equipment conditions. Highlights: IMU sensor array proposed as a means to measure warfighter aiming performance. IMU array detected decreases in warfighter aiming performance as a result of fatigue. IMUs are effective at pre/post comparisons of fatigue, load and equipment variations. IMUs have wide applicability, including: athletics, rehabilitation, and performance.